Peroxydisulfate as an Oxidant in the Site‐Selective Functionalization of sp3 C–H Bonds. Issue 33 (22nd November 2017) - Sathyamoorthi, Shyam; Banerjee, Shibdas
Abstract: The development of methodology for the site‐selective functionalization of sp 3 C–H bonds has irrevocably altered the state of organic synthesis. These methods often rely on the use of strong oxidants in conjunction with transition‐metal catalysis. Peroxydisulfate (S2 O8 2– ) salts are some of the strongest inorganic oxidants known. They are low‐cost crystalline solids that are stable at room temperature. Harmless sulfate salts are produced as a byproduct of their reactions, allowing S2 O8 2– to serve as a 'green' alternative to other commonly employed oxidants. Despite these attractive properties, it has only been in the last ten years that the majority of sp 3 C–H functionalization reactions utilizing S2 O8 2– for the diversification of complex molecules have been reported. The objective of this review is to provide a useful reference regarding the recent advancement of sp 3 C–H functionalization using S2 O8 2– and to inspire the invention of new protocols utilizing this remarkable oxidant. Abstract : This review article highlights the use of peroxydisulfate salts for the conversion of sp 3 C–H into C–O, C–C, C–N, and C–S bonds. Despite being low‐cost, powerful, and ecologically‐friendly, peroxydisulfate salts remain underutilized in sp 3 C–H functionalization reactions. This review will provide a useful reference for researchers interested in developing new reactions with these remarkable oxidants.